Vocabulary Profiling Of EFL Students’ Descriptive And Recount Texts: A Focus On Word Levels And Pedagogical Implications - Mulyani, Euis Rina (Universitas Negeri Medan, 2025)
This study examines the vocabulary profile of EFL students’ written artifacts, produced as part of writing assignments during the early stage of their academic writing courses. Fourteen texts written by seven students were analyzed using the Lextutor Vocabulary Profiler. The analysis focused on frequency bands including K1, K2, the Academic Word List (AWL), and Off-list words. The findings revealed that both genres were heavily dominated by K1 words, with recount texts showing a higher percentage (79.26%) than descriptive texts (74.16%). Descriptive texts exhibited greater lexical variation, reflected in their higher proportions of AWL words (5.76% vs. 1.86%) and Off-list items (13.71% vs. 10.00%). Meanwhile, recount texts contained more K2 words (8.89%) than descriptive ones (6.37%). These findings suggest that recount texts tend to rely on basic narrative vocabulary, while descriptive texts invite more diverse lexical choices, including academic and culturally specific terms. The overall underuse of academic vocabulary across both genres points to the need for explicit, genre-sensitive vocabulary instruction. Pedagogically, the results support integrating vocabulary profiling into EFL writing instruction to guide differentiated teaching, foster morphological awareness, and promote genre-appropriate lexical development.